Potensi Bahan Alam di Banyumas Sebagai Agen Untuk Mempercepat Penyembuhan Luka Jaringan Lunak Rongga Mulut - Rambiati, Wahyu Intan Putri; Sunaryono, Rizqi Amalia; Husna, Neneng Syifa Sofiyatul; Yuliani, Ananda Putri; Taqwim, Ali (Journal of Dental and Biosciences, 2025)
Background: Wounds in the oral cavity are something that cannot be avoided in dental practice, especially in several procedures such as incisions, excisions and gingivectomy. The wound healing process takes a long time, increasing the risk of infection, which will hinder the healing process. The main focus in treating wounds is fast healing with optimal results. Currently, it is necessary to develop alternatives for the use of natural ingredients that can speed up the wound healing process with minimal side effects. Objective: The purpose of writing this article is to explore the potential of natural ingredients in Banyumas which have the effect of accelerating the healing of soft tissue wounds in the oral cavity. Method: This literature review source search method refers to reference sources in the form of PubMed and Google Scholar and then data analysis is carried out according to the specified topic. Result: Natural ingredients that are widely produced in Banyumas include cinnamon leaves (Cinnamomum verum), red ginger rhizomes (Zingiber officinale Var Rubrum rhizoma), turmeric (Curcuma longa Linn.), bay leaves (Syzygium polyanthum), aloe vera (Aloe vera L.) , robusta coffee (Coffea canephora), papaya leaves (Carica papaya L.), red dragon fruit (Hylocereus polyrhizus), and land snail mucus (Achantina fulica) contain active ingredients that can accelerate the healing of soft tissue wounds in the oral cavity. Conclusion: There are natural ingredients in Banyumas that contain active ingredients that can accelerate the healing of soft tissue wounds in the oral cavity.